Future applications of high-resolution MS to meet the demands for pain management drug testing. (November 2014) - Crews, Bridgit O
Urine specimens submitted for pain management drug testing often contain multiple psychotherapeutic drugs, in addition to opioids. Immunoassay-based screen-and-confirm approaches typically used for clinical drug testing have limited sensitivity to detect therapeutic concentrations of many drugs prescribed in pain management and do not differentiate between drugs in the same class. In addition, screening for all the various illicit and prescription drugs that may be present in the pain management population requires as many as 10–20 individual immunoassays. High-resolution MS approaches have the potential to transform the way clinical drug testing is performed for pain management.